Життєздатність Picea abies (L.) Karst. у насадженнях м. Кривого Рогу (Степова зона України) - Korshykov, I.I.; Huseynova, E.R. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to investigate the viability of Picea abies (L.) Karst. in Kryvyi Rih plantations. Material and methods. Viability of P. abies in plantations on 8 plots with different stage of anthropogenic pollution. 30 trees of 30–40 years were studied at each site. The distance from the road to the plot and between the trees was taken into account. The approximate age of the trees was determined by the number of whorls and external features (the color of the needles, the shape of the crown, the height of the tree and the diameter of the trunk). Results. We ascertained that 34–38-year-old plants on the background levels of aerotechnogenic pollution (arboretum of botanical garden, parks) were well developed, their height was 13.6–14.8 m and trunk diameter – 26.2–28.5 cm. The growth of trees of the same which are near smelters is suppressed (height was 10.4–10.9 m, trunk dia meter – 20.3–22.1 cm), as well such trees have damages and dieback (57.8 %). Fewer such trees (36.3 %) are occurred in clumps near the city roads with high motor traffic. Dense plantations of P. abies (between plants – distance 0.5–4.0 m) cause 24–35-year-old trees in the center of the curtain to inhibition. Conclusion. P. abies may be used in the large industrial cities of Dnieper Ukraine for road greenery at distance of 10 m from roads in curtain stands, adjoining areas, squares and parks.